A study on effectiveness of integrated shop houses resident to the owner / resident / Mohd Erwan Ismail - Ismail, Mohd Erwan (Faculty of Architecture, Planning and Surveying, 2009)
In recent years, more Malaysians are moving into mixed development, especially in urban centers due to limited land availability. Thus, there is a greater awareness of the need for these properties to be well-managed for resident satisfaction. Management has historically been underrated and is often associated with mundane maintenance work. However, with the increasing development of mixed property, there has been an increasing demand and complaint by residents. Therefore, this study has been developed with aim to identify the comfortable level in shop houses buildings, identifying die problems exist in the shop houses and identifying role and function of maintenance management cooperate to overcome the problems in shop houses. The study was conducted through questionnaire with resident, structured interview with professional maintenance management, and also through site survey. From the study, it found that the comfortable issues faced by tenant, major problems in shop houses and maintenance approach and actions in solved the problems faced by residents. Generally, the development of shop houses also needs the developer thinking towards improving and providing a better life in term in comfortable and satisfaction in properties management. Realizing the importance of to improve the life quality in shop houses* tins dissertation which titled “A Study on Effectiveness of Integrated Shop Hoses Resident to The Owner/Residents” is documented.